Development of Authentic Assessment Instruments in PJBL in Fine Arts Learning for Grade 4 at Muhammadiyah 4 Elementary School, Malang City - Fardana, Yudistira; Pantiwati, Yuni (Universitas Nusantara PGRI Kediri, 2025)
This study aims to develop an authentic assessment instrument for Project-Based Learning (PJBL) in Fine Arts for fourth grade elementary school students. This instrument is designed to comprehensively assess the process and results of students' work, particularly in the activities of designing and designing lesson schedules as visual art products. The study used the Research and Development (R&D) method with the stages of needs analysis, instrument design, expert validation, and limited classroom trials. The results show that the developed instrument is valid and feasible to use, and is able to effectively measure aspects of creativity, technical skills, and student cooperation attitudes. This instrument is recommended as a contextual assessment tool that can support the implementation of more meaningful and comprehensive PJBL learning at the elementary school level.